Effect of neutron irradiation on ductility of tungsten foils developed for tungsten-copper laminates. (March 2022) - Zinovev, Aleksandr; Terentyev, Dmitry; Chang, Chih-Cheng; Yin, Chao; Bakaev, Alexander; Rieth, Michael; Lied, Philipp; Reiser, Jens; Bonnekoh, Carsten
Highlights: DBTT shift in rolled W foil irradiated to 0.15 dpa at 400 °C does not exceed 50 °C. DBTT shift in bulk W irradiated to 0.15 dpa at 400 °C amounts to 200…250 °C. DFT study shows a possibility of diffusion of Cu atoms to W in a W-Cu composite. Abstract: Severe plastic deformation of tungsten (W) is known to be an efficient way to reduce its inherently high ductile-to-brittle transition temperature (DBTT), what is essential for its use in components of a fusion reactor. Thin rolled W foils possess superior mechanical behaviour at room temperature (RT), as demonstrated in previous works. It was then proposed to expand the beneficial mechanical properties of the foil to bulk by fabricating tungsten-copper (W-Cu) laminate composites, which can be used for structural applications. Neutron irradiation in HFIR resulted in embrittlement of the laminate already after 0.016 dpa, with the W foil determining the composite behaviour. In this work, for the first time, we investigate the effect of neutron irradiation on individual W foil, and determine the resulting DBTT shift with the help of cantilever bend tests, using bulk W and the W-Cu composite as reference. The W foil and the bulk samples were irradiated to 0.15 dpa at 400 °C in the BR-2 reactor in Mol (Belgium). We also hypothesise that diffusion of Cu atoms into W could modify the response to irradiation in these materials. We substantiate it with complementary density functional theory (DFT) ab initio calculations to analyse the Cu-vacancy and Cu-self-interstitial interaction, which helps to elucidate co-alignment of the fluxes of point defects and Cu solutes in W matrix. Irradiated foil was found to retain its ductility at RT. No significant irradiation hardening or DBTT shift were detected in the irradiated W foil compared to the bulk W. The different irradiation effect on embrittlement in individual foils and in the laminate may be attributed to the irradiation-assisted diffusion of Cu solutes in W foil, which could form intermetallic phases and affect the accumulation of lattice defects.